Minat Wisatawan Berkunjung ke Kota Jakarta, Indonesia - Dira Oktavia, Reno Catelya; Swantari, Anita; Hutagalung, Muhammad Husen; Suprina, Rina; Darsiah, Anis (Jurnal Ilmiah Pariwisata, 2025)
This study aims to analyze the factors that influence tourists' interest in visiting Jakarta, with a focus on shopping destinations, cultural and historical attractions, culinary tourism, and nightlife. The method used is a quantitative approach with a population of all visitors to Jakarta, both domestic and foreign. The research sample was 200 respondents selected by purposive sampling. Data were collected through questionnaires and analyzed using multiple regression. The results of the study showed that all variables tested (shopping destinations, cultural and historical attractions, culinary tourism, and nightlife) have a significant influence on tourists' interest in visiting Jakarta. The shopping destination factor has the greatest influence, followed by cultural and historical attractions, culinary tourism, and nightlife. Based on these results, it can be concluded that Jakarta has great potential to attract more tourists through the development of these sectors. The advice given to tourism destination managers and local governments is to continue to improve facilities and promotions related to shopping, cultural, culinary, and nightlife tourism in order to strengthen Jakarta's appeal as a major tourist destination, and so that tourists can explore more aspects of the city during their visit. Keywords: shopping destinations, cultural and historical attractions, culinary tourism, nightlife, interest in visiting